Analysis of upper limb muscles properties in elite swimmers before and after training - Koo, R. K.; Kang, H.; Park, S. W.; Kim, T. (Korean Journal of Sport Biomechanics, 2023)
Objective: The aim of this study is to verify the differences in muscle characteristics of elite level swimmers before and after a 2-hour practice session. Method: The study was conducted on 15 elite swimmers. Preliminary measurements for each muscle (Anterior Deltoid, Triceps Brachii, Biceps Brachii, Flexor Carpi Ulnaris) were taken using the MyotonPRO device before training. After approximately 2 hours of training, the same muscle areas were measured again. The collected data was analyzed through descriptive statistics and two-way 2×2 RG·RM ANOVA, and all statistical significance levels were set at a=.05. Results: After analyzing the characteristics of the Flexor Carpi Ulnaris (FCU) before and after training in both proficiency level swimmers (excellent, non-excellent), it was found that the interaction effect of group X repetition in muscle tension (F), muscle stiffness (S), and body recovery time (R) was statistically significant. Secondly, in the analysis of the Biceps Brachii (BB), the main effect of repetition in muscle tension (F), muscle stiffness (S), and body recovery time (R) was statistically significant. Furthermore, the interaction effect of group X repetition in muscle stiffness (S) and body recovery time (R) was statistically significant. Conclusion: The efficient use of FCU and BB suggests that it is an important factor distinguishing the performance of excellent and non-excellent swimmers in swimming. Therefore, if we develop and apply measures to efficiently utilize FCU and BB during training, it can help improve the performance of the athletes.